KETERLIBATAN UMAT DEWASA DALAM IBADAT SABDA MINGGU DI STASI ST. CAECILIA BERIBIT PAROKI ST. EUGENINUS DE MAZENOD - Dewi, Elisabeth Novi Saputri; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
This study explores the involvement of adult parishioners in the Sunday’s Liturgy of the Word Celebration at St. Cecilia Basic Christian Community in Beribit, Paroki St. Eugeninus de Mazenod, Diocese of Tanjung Selor. The main objective of this research is to examine the factors affecting the low attendance of adult members in the celebration and to understand the underlying issues contributing to this phenomenon. The study highlights that the Sunday’s Liturgy of the Word Celebration is crucial for both the faith formation of the parishioners and the fostering of a pastoral spirit among adults. However, many adult members refrain from attending the service due to low awareness of its significance. This qualitative study uses structured interviews as its primary data collection method, with purposive sampling employed to select informants. Data analysis follows an inductive approach. The findings reveal that the low participation of adults is primarily due to a lack of understanding regarding the importance of the Liturgy of the Word Celebration and resistance to the involvement of lay leaders in the service.